2006
DOI: 10.1111/j.1464-410x.2006.06153.x
|View full text |Cite
|
Sign up to set email alerts
|

Prostate stem cell antigen predicts tumour recurrence in superficial transitional cell carcinoma of the urinary bladder

Abstract: OBJECTIVES To evaluate the relationship between prostate stem cell antigen (PSCA) expression level in transitional cell carcinoma (TCC) of the urinary bladder and various clinicopathological features, including stage and grade; and to determine whether PSCA mRNA expression predicts disease recurrence in superficial (not muscle‐invasive) TCC of the bladder. PATIENTS AND METHODS Real‐time reverse transcriptase‐polymerase chain reaction (RT‐PCR) was performed on 97 TCC tissue samples and in 36 samples of normal b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 15 publications
3
27
0
Order By: Relevance
“…Previous studies have shown that PSCA was initially identified as a prostate-specific cell-surface antigen (Argani et al, 2001), and that it is highly expressed in prostate cancer and other non-prostatic malignancies, such as gastric cancer, pancreatic cancer, and bladder cancer (Elsamman et al, 2006;Grubbs et al, 2006). Studies have also reported the differential expression of PSCA in these tumors, and significant discrepancies among its genetic polymorphisms (Elsamman et al, 2006;Feng et al, 2008). Among these variants, rs2294008 (C>T) is the most widely studied.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that PSCA was initially identified as a prostate-specific cell-surface antigen (Argani et al, 2001), and that it is highly expressed in prostate cancer and other non-prostatic malignancies, such as gastric cancer, pancreatic cancer, and bladder cancer (Elsamman et al, 2006;Grubbs et al, 2006). Studies have also reported the differential expression of PSCA in these tumors, and significant discrepancies among its genetic polymorphisms (Elsamman et al, 2006;Feng et al, 2008). Among these variants, rs2294008 (C>T) is the most widely studied.…”
Section: Discussionmentioning
confidence: 99%
“…8 Several other non-prostatic malignancies including bladder cancer, clear renal cell cancer, pancreatic cancer and gastric cancer were identified to express PSCA as well. [9][10][11][12] It has been found that PSCA is expressed in differentiating gastric epithelial cells, has a cell-proliferation inhibition activity in vitro and is frequently silenced in gastric cancer. 12 In normal stomach, PSCA is expressed at the isthmus of the gastric gland, which may harbor proliferating precursor cells, and may inhibit cell proliferation acting as a tumor suppressor.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, several othertumorswereevaluatedforPSCAexpressionincluding pancreatic adenocarcinoma [10][11][12], transitional cell carcinoma [9,13],renalcellcarcinoma [14],anddiffuse-typegastriccancer [15].…”
Section: Introductionmentioning
confidence: 99%